Organize user's manual. - Schwartz, Helen J. (Wadsworth Pub. Co., 1987)
An idea-generation and organization program that helps student writers write strong, well-written essays by narrowing and clarifying their topics, deciding on appropriate developmental strategies, and putting together detailed working outlines.